PENGABDIAN DESA MELALUI PEMBUATAN DAN PEMUTARAN FILM DOKUMENTER DI KELURAHAN REBAH TINGGI KOTA PAGARALAM - Annada Nasyaya,; Agung Osama Dillah,; Auliya Al Muhsonna,; Muhammad Reynaldi Agustian,; Putri Azzahra,; Putri Iswa Nabilah,; Zega, Prima Harlit; Rahmad Hidayah Abellah, (JURNAL PENGABDIAN MANDIRI, 2024)
Indonesia is a country with a variety of uniqueness, this cannot be separated from the various tribes, races, customs and cultures that were born and spread throughout the archipelago. Likewise in one of the sub-districts in Pagar Alam City, namely Reba Tinggi Sub-district. Born and grown as a sub-district with history and customs that are still inherent in the local community. Therefore, the Reba Tinggi Subdistrict PMD Team took the initiative to visualize this in a documentary film containing history, traditional figures, culture and many other things that are customary in the subdistrict. This documentary film was made based on a well-planned framework from the pre-production section which prepared all kinds of concepts and ideas and various kinds of manufacturing permits to smooth the production process, then to the production process where there were many shooting areas and interviews with traditional leaders and residents for data. valid, up to quite complex post-production. This documentary film was made with the aim of increasing knowledge about the history and existence of Reba Tinggi Village so that future generations can enjoy various kinds of local wisdom in Reba Tinggi Village.